LncRNA HOTAIR promotes the growth and metastasis of gastric cancer by sponging miR-1277-5p and upregulating COL5A1 - Wei, Zhijian; Chen, Lei; Meng, Lei; Han, Wenxiu; Huang, Lei; Xu, Aman (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2020)
Background Emerging studies have shown that HOTAIR acts as an oncogene in gastric cancer (GC). However, its role in the extracellular matrix and in tumor immune infiltration remains unknown. Methods HOTAIR and COL5A1 levels were analyzed by bioinformatics analysis and validated by qRT-PCR, western blotting and immunohistochemistry assays. The regulatory relationships between components of the HOTAIR/miR-1277-5p/COL5A1 axis and the role of this axis in GC were predicted by bioinformatics analysis, and validated by in vitro and in vivo experiments. The correlation between COL5A1 and GC immune infiltration was assessed by bioinformatics analysis and a COL5A1-based predictive nomogram was established using the Stomach Adenocarcinoma dataset from The Cancer Genome Atlas. Results We found that HOTAIR and COL5A1 were overexpressed in GC compared to normal controls, which predicted poor prognosis. The regulatory relationship of the HOTAIR/miR-1277-5p/COL5A1 axis in GC was demonstrated, and HOTAIR and COL5A1 were found to promote GC growth while miR-1277-5p exerted the reverse effects. In addition, COL5A1 was negatively associated with tumor purity but positively associated with immune infiltration, which suggested that COL5A1-mediated GC growth may be partially mediated by the regulation of immune infiltration. Additionally, the established COL5A1-based nomogram showed that COL5A1 can serve as a prognostic biomarker in GC. Conclusions HOTAIR regulates GC growth by sponging miR-1277-5p and upregulating COL5A1, and COL5A1-mediated GC cell proliferation may be mediated by effects on the tumor microenvironment, which provides novel targets for GC treatment.